Meteorological observations from German military weather stations on Svalbard, 1941–1945 - B.-M. Sinnhuber (Polarforschung, 2024)
During World War II, the German Kriegsmarine and Luftwaffe operated a series of weather stations on Svalbard between 1941 and 1945 to obtain information on synoptic weather situations in the Arctic. These activities also included some of the first automatic weather stations. With a few exceptions, the meteorological observations from these military stations are regarded as lost. Most of these observations could now be retrieved from weather maps of the German Zentrale Wetterdienstgruppe (ZWG) that are preserved in the archives of the Deutscher Wetterdienst (DWD). Reports of surface pressure and temperature have been digitized for the military weather stations Bansö in 1941/42, Knospe in 1941/42, Nussbaum in 1942/43, Kreuzritter in 1943/44, and Svartisen in 1943/44 and for automatic weather stations operated on Svalbard. These data can help to close the existing gap in the Svalbard climate record for 1941–1945 and to provide additional observational constraints for future climate reanalysis. These data also provide a new perspective on the history of the German meteorological activities in the Arctic during World War II by showing the impact these observations had on the meteorological analyses. In this sense, this paper also tries to bridge the gap between climate research and history.